The Influence of Search Engine Optimization and Brand Awareness on Consumer Purchase Intentions: Study on Body Shop Products - Erawan, Ida Ayu Shanti Pinandita; Telagawathi, Ni Luh Wayan Sayang; Winata, I Gusti Ketut Adi; Suarmaja, Ida Bagus Koman (Universitas Pendidikan Ganesha, 2025)
Brand Awareness also plays an important role in shaping consumer perceptions of a product. However, there is still uncertainty about the extent to which these two factors, SEO and Brand Awareness, are able to influence consumer purchase intentions. Therefore, this study aims to identify and analyze the influence of SEO and Brand Awareness on consumer purchase intentions, especially on The Body Shop products. The research method used is multiple linear regression, with data collection from 100 selected respondents using the quota sampling method. Data analysis was carried out using SPSS software version 20. The results of the study showed that search engine optimization and brand awareness have a positive and significant effect on consumer purchase intentions. In conclusion, digital marketing strategies through search engine optimization and strengthening brand awareness have proven effective in increasing consumer purchasing decisions for The Body Shop products. Therefore, companies are advised to continue to develop digital marketing strategies, especially through search engine optimization and campaigns that increase brand awareness to maintain competitiveness and encourage consumer purchase intentions.